2021
DOI: 10.1101/2021.08.19.456093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneity of the Cancer Cell Line Metabolic Landscape

Abstract: The unravelling of the complexity of cellular metabolism is in its infancy. Cancer-associated genetic alterations may result in changes to cellular metabolism that aid in understanding phenotypic changes, reveal detectable metabolic signatures, or elucidate vulnerabilities to particular drugs. To understand cancer-associated metabolic transformation we performed untargeted metabolite analysis of 173 different cancer cell lines from 11 different tissues under constant conditions for 1099 different species using… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 62 publications
1
1
0
Order By: Relevance
“…However, there were some instances where cell lines from the same tissue origin clustered together, such as Cluster 3 that was enriched with prostate cancer cells and Cluster 4 with endometrial cancer cells (Fig 1B), which has been observed in another pan-cancer metabolome study (Shorthouse et al, 2022). Despite the identification of heterogeneous clusters of cells based upon the levels of metabolites of high flux pathways, there was no clear organization of these metabolites into pathways (Fig 1B), likely because strong metabolite interactions are often localized at the reaction level (Benedetti et al, 2023), that could underpin a testable hypothesis centered on differences and similarities of pathway activity.…”
Section: All Clusters Contained Tumor and Normal Cell Lines From Diff...supporting
confidence: 59%
See 1 more Smart Citation
“…However, there were some instances where cell lines from the same tissue origin clustered together, such as Cluster 3 that was enriched with prostate cancer cells and Cluster 4 with endometrial cancer cells (Fig 1B), which has been observed in another pan-cancer metabolome study (Shorthouse et al, 2022). Despite the identification of heterogeneous clusters of cells based upon the levels of metabolites of high flux pathways, there was no clear organization of these metabolites into pathways (Fig 1B), likely because strong metabolite interactions are often localized at the reaction level (Benedetti et al, 2023), that could underpin a testable hypothesis centered on differences and similarities of pathway activity.…”
Section: All Clusters Contained Tumor and Normal Cell Lines From Diff...supporting
confidence: 59%
“…More recently, several publications have reported the outcomes of high-throughput metabolomics using pan-cancer cell line panels, such as the NCI-60 (60 cell lines, Jain et al, 2012;Ortmayr et al, 2019) and CCLE panels (928 cell lines, Li et al, 2019), CAMP (988 tissue samples, Benedetti et al, 2023), and other panels containing 180 cell lines (Cherkaoui et al, 2022), and 173 cell lines (Shorthouse et al, 2022). These studies primarily aimed to identify links between cancer cell metabolic phenotypes and transcriptional regulation (Benedetti et al, 2023;Ortmayr et al, 2019), or genetic alterations and dependencies (Li et al, 2019;Mullen & Singh, 2023) that were associated with drug-sensitivities (Shorthouse et al, 2022). Notably, Cherkaoui and colleagues (2022) took a top-down approach by clustering the metabolome acquired by untargeted metabolomics across 49 KEGG metabolic pathways of 180 cancer cells.…”
Section: Introductionmentioning
confidence: 99%